Analisis Karakteristik Perusahaan Dan Ekonomi Makro Pada Return Saham Syariah Dan Non Syariah - Ardi Hamzah (Jurusan Akuntansi Fakultas Ekonomi Universitas Negeri Surabaya, 2011)
AbstractThe objectives of this paper are to determine, to examine, and to test whether firm characteristic and macro economics are the important discriminators for return of syariah and non syariah stock; to determine whether there are any differences in return of some syariah and non syariah stock; to determine and to test whether there is a relationship between return and firm characteristic and macro economis in some syariah and non syariah stock. The total sample is 300 stock that were taken each from 150 for syariah stock and 150 for non syariah stock for period 2005 2009. The study also showed that there is a difference in return between syariah and non syariah stock. Finally,with regression analysis indicated that partially price book value, price earnings ratio, and kurs rupiah on dollar significantly effect on return of syariah stock, while for return of non syariah stock only kurs rupiah on dollar that significantly effect on return of non syariah stock. For testing with simultant regression indicate firm characteristic and macro economics significantly effect on return of syariah stock, while at return of non syariah stock not significantly effect.